2019
DOI: 10.1186/s12864-019-5567-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in secondary metabolite production potential in the Fusarium incarnatum-equiseti species complex revealed by comparative analysis of 13 genomes

Abstract: Background The Fusarium incarnatum - equiseti species complex (FIESC) comprises 33 phylogenetically distinct species that have been recovered from diverse biological sources, but have been most often isolated from agricultural plants and soils. Collectively, members of FIESC can produce diverse mycotoxins. However, because the species diversity of FIESC has been recognized only recently, the potential of species to cause mycotoxin contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 83 publications
(152 reference statements)
6
56
2
1
Order By: Relevance
“…The presence of homologous SAM clusters in the Dothideomycetes, Eurotiomycetes, Lecanoromycetes and Sordariomycetes indicate that HGT of SAM clusters could have occurred between fungal genera and even between classes of fungi. Together, the inferences of HGT of SAM clusters among fusaria reported in the current study and inferences of HGT of PKS and nonribosomal peptide synthetase genes between members of the F. incarnatumequiseti species complex and other lineages of Fusarium [49] provide evidence that HGT has significantly impacted the distribution of secondary metabolite biosynthetic genes and, therefore, production of secondary metabolites in Fusarium.…”
Section: The Discontinuous Distribution Of the Sam Clusters Insupporting
confidence: 71%
See 1 more Smart Citation
“…The presence of homologous SAM clusters in the Dothideomycetes, Eurotiomycetes, Lecanoromycetes and Sordariomycetes indicate that HGT of SAM clusters could have occurred between fungal genera and even between classes of fungi. Together, the inferences of HGT of SAM clusters among fusaria reported in the current study and inferences of HGT of PKS and nonribosomal peptide synthetase genes between members of the F. incarnatumequiseti species complex and other lineages of Fusarium [49] provide evidence that HGT has significantly impacted the distribution of secondary metabolite biosynthetic genes and, therefore, production of secondary metabolites in Fusarium.…”
Section: The Discontinuous Distribution Of the Sam Clusters Insupporting
confidence: 71%
“…We used previously described approaches [18,49] to assess the potential contribution of HGT to the discontinuous distribution of SAM clusters among Fusarium species. The approaches were: 1) reconciliation analysis with the program NOTUNG, which infers HGT, duplication or loss of genes to reconcile branch conflicts between gene trees and species trees; 2) constraint analysis with the Shimodaira-Hasegawa and Approximately Unbiased (SH-AU) tests; and 3) estimates of synonymous site divergence.…”
Section: Contributors To Discontinuous Distribution Of Sam Clustersmentioning
confidence: 99%
“…This number is nearly the double of the reported HGT frequency of 4% for metabolic enzymes (Wisecaver et al, 2014), but is much lower than the 25-35% reported for SM gene clusters by Marcet-Houben and Gabaldón (2019). Manual inspection of inferred HGTs in our study suggests that the total number of events is actually overestimated by reconciliation software like NOTUNG, which has been recently reported (Villani et al, 2019). The weak support of certain branches is likely due to accelerated evolution in certain fungal species, as exemplified with Z. cellare (Zasce1) in clade 1 and P. niveus (Bysni1) in clade 7.…”
Section: Discussioncontrasting
confidence: 60%
“…Eight Aspergillus species covering four sections were recovered in this study: Samson et al, 2007;Perrone et al, 2011;Varga et al, 2011). The Fusarium isolates comprised two species (F. chlamydosporum and F. incarnatum/equiseti species complex; O' Donnell et al, 2013;Villani et al, 2019) and one unresolvable species reported here as Fusarium sp. The Penicillia were clustered into four sections: Charlesia (P. coffeae; Visagie et al, 2014c), Citrina (P. citrinum, P. copticola, P. paxilli, and P. steckii; Visagie et al, 2014b), Lanata-Divaricata (P. rolfsii; , and Sclerotiora (P. sclerotiorum; Rivera and Seifert, 2011;Visagie et al, 2014b).…”
Section: Fungal Occurrence (Load and Incidence) In Dried Rte Foods Anmentioning
confidence: 99%